Philippe Parreno - Anywhen - Lissoni, Andrea 1970- (Tate Publishing, 2016)
Philippe Parreno is a leading French artist who works across film, video, sound, sculpture, performance and information technology. His work explores the borders between reality and fiction, and he sees his exhibitions as choreographed spaces that follow a score, during which a series of different events unfold. These kaleidoscopic environments redefine the gallery-going experience. Having collaborated with many visual artists as well as musicians, architects, scientists and writers, Parreno continues the tradition of the avant-garde artist engaged with many cultural disciplines. Created in collaboration with the artist, the book features a fully illustrated survey of Parreno's life and work and an interview with curator Andrea Lissoni. Exploring the artistic processes involved in creating his work, it includes photographs of Parreno's new installation that is exhibited in the Turbine Hall for this exhibition
Published on occasion of the second annual Hyundai Commission's exhibition "Philippe Parreno - Anywhen", held at the Tate Modern, London, 4 October 2016 - 2 April 2017
Keywords: Parreno, Philippe -- 1964-; Videokunst; Performance -- Künste; Parreno, Philippe 1964-; Ausstellungskatalog -- Tate Modern -- 04.10.2016-02.04.2017 -- London